Design of IoT-Based Smart Charging Power Supply for Pratima Security - Cahaya Risna, Komang Sadewa; I Nyoman Piarsa; AA.Kt.Agung Cahyawan Wiranatha (JITTER: Jurnal Ilmiah Teknologi dan Komputer, 2025)
A power supply is essential for the Pratima security system because it serves as the primary energy source that ensures all components of the Pratima security system can operate optimally, especially during power outages. This study designs a power supply system with a smart charging feature for the IoT-based Pratima security system. This system uses an ESP8266 microcontroller, current and voltage sensors, and is connected to the Telegram application to provide notifications when the 18650 battery is full. Unlike previous studies that utilize websites, this system offers a simpler and more efficient monitoring solution via Telegram. The goal is to maintain the quality of the 18650 battery, prevent overcharging, and provide a power reserve to keep the security system active. This study uses the Software Development Life Cycle (SDLC) method with a Waterfall model consisting of 5 stages: analysis, design, implementation, testing, and maintenance. The results of this study are expected to be an alternative power supply with a smart charging feature at an affordable price and can be applied to other IoT devices that require an automatic and efficient charging system.